Bone Grafting: Sourcing, Timing, Strategies, and Alternatives. (December 2015) - Egol, Kenneth A.; Nauth, Aaron; Lee, Mark; Pape, Hans-Christoph; Watson, J. Tracy; Borrelli, Joseph
Abstract : Summary: Acute fractures, nonunions, and nonunions with bone defects or osteomyelitis often need bone graft to facilitate union. There are several factors to consider when it is determined that a bone graft is needed. These factors include the source of the bone graft (autograft vs. allograft), proper timing for placement of the bone graft, strategies to avoid further complications (particularly in the setting of osteomyelitis), and with the development of a variety of bone graft substitutes, whether alternatives to autograft are available and appropriate for the task at hand. Autograft bone has commonly been referred to as the "gold standard" of bone grafts, against which the efficacy of other grafts has been measured. The best timing for when to place a bone graft or substitute is also somewhat controversial, particularly after an open fracture or a potentially contaminated bed. The treatment of infected nonunions, particularly those that require a graft to facilitate healing, can be quite challenging. Typically, the infection is completely eradicated before placement of a bone graft, but achieving a sterile bed and the timing of a bone graft require strategic thinking and planning. This review outlines the benefits of autografts, the most suitable sites for harvesting bone grafts, the timing of bone graft procedures, the potential risks and benefits of grafting in the face of infection, and the currently available bone graft extenders.